Improving Your C# Skills : Solve Modern Challenges with Functional Programming and Test-Driven Techniques of C#. - Mehboob Ahmed Khan, Ovais (Packt Publishing Ltd, 2019)
With this Learning Path, you will be able to easily solve complex programming challenges using advanced features of C#. You'll structure and build scalable, optimized, and robust applications in C#7 and .NET, and with the newly-acquired TDD skills, you'll be ready to enter the market not only as a C# pro, but also as a TDD expert.